Relationship Between Environmental Knowledge, Pro-Environmental Attitude, and Pro-Environmental Behavior of Employees (Study at PT X) - Lalu Muhammad, Aby Dujana; Soesilo, Tri Edhi Budhi; Fatmah, (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
The rapid industrialization has led to environmental degradation, exacerbated by a lack of pro-environmental behavior. This study aimed to analyze the correlation between environmental knowledge, pro-environmental attitudes, and pro-environmental behavior within the industrial sector. The study was conducted at the workshop of PT X, an Indonesian mining services company with operations across the country. A quantitative research method was employed using simple random sampling to select respondents who completed questionnaires. The data were analyzed using a product moment correlation coefficient test. The results indicated no significant correlation between environmental knowledge, pro-environmental attitudes, and pro-environmental behaviors. However, a significant relationship was found between years of service and the level of environmental knowledge among participants. This suggests that knowledge and attitudes alone are insufficient to promote pro-environmental behavior. Further research is needed to identify these factors and design more effective interventions to promote sustainable industrial practices and mitigate the negative impacts of industrialization.